2021
DOI: 10.2147/idr.s295801
|View full text |Cite
|
Sign up to set email alerts
|

First Identification of a Patient with Prosthesis-Related Infection Caused by an MCR-1.1-Producing ST131 Escherichia coli After Rhinoplasty

Abstract: Background:The most common procedure of rhinoplasty is the implantation of a synthetic prosthesis. However, the complications, especially postoperative infection, could lead the suboptimal aesthetic outcome, economic losses and health threats. There is currently little literature providing an incidence of rhinoplasty infection and microbiological and antimicrobial resistance situations. Methods: Therefore, we performed a retrospective observational study which included 173 patients who received a rhinoplasty f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In this context, the pandemic Escherichia coli sequence type 131 (ST131) carrying mcr-type genes has emerged causing extraintestinal infections (Liu et al, 2018;Mamani et al, 2019;Reid et al, 2019;Li et al, 2021). The complex subclonal structure of ST131 elucidated three major clades, each associated with a specific allele of the type 1 fimbrial adhesin gene (fimH), namely clade A with fimH41, clade B with fimH22, and clade C with fimH30 (Petty et al, 2014;Stoesser et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the pandemic Escherichia coli sequence type 131 (ST131) carrying mcr-type genes has emerged causing extraintestinal infections (Liu et al, 2018;Mamani et al, 2019;Reid et al, 2019;Li et al, 2021). The complex subclonal structure of ST131 elucidated three major clades, each associated with a specific allele of the type 1 fimbrial adhesin gene (fimH), namely clade A with fimH41, clade B with fimH22, and clade C with fimH30 (Petty et al, 2014;Stoesser et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Infection is the most serious complication after rhinoplasty 6 . Processes such as, osteotomies, performed during rhinoplasty breach the periosteum or nasal mucosa, creating a potential route for the spread of infection, which can lead to unsuccessful plastic surgery 7 . The cause of bleeding during rhinoplasty is damage to the large vessels at the site of osteotomy, or damage to the small subdermal vessels during osteotomy 8 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the infection problem still cannot be ignored. Previous studies reported that the infection rate was about 2.5%, other studies reported the rate was ∼6% 8–10. The infection incidents may injure the emotion and health of patients, and gain additional economic burden.…”
mentioning
confidence: 97%
“…Previous studies reported that the infection rate was about 2.5%, other studies reported the rate was ∼6%. [8][9][10] The infection incidents may injure the emotion and health of patients, and gain additional economic burden. The risk factors on infection after rhinoplasty with autologous costal cartilage transplantation include stacked grafts, revision cases, excessive skin stretching, and previous alloplast-related infections.…”
mentioning
confidence: 99%
See 1 more Smart Citation